EFEKTIVITAS KRIM FORMULASI TEH HIJAU (Camellia sinensis) SEBAGAI AGEN ANTIBAKTERI TERHADAP PATOGEN KULIT - Prayogo, Fitra Adi; Wijayanti, Heni; Rahmawati, Novita; Budiharjo, Anto; Wulandari, Dyah (Universitas Diponegoro, 2025)
This research aims to determine the effect of green tea extract cream 6%, 8%, and 10% w/w against Staphylococcus epidermidis and Propionibacterium acne. The method begins with making green tea extract using the maceration method, and qualitative flavonoid, alkaloid, saponin, and tannin tests are carried out. Next, S. epidermidis and P. acnes were rejuvenated on NA media and cultured at 37°C for 24 hours. Both bacteria were then inoculated into different test tubes containing 0.9% NaCl. The suspension was then vortexed, and the turbidity level was equalized with McFarland's solution. Both bacteria were then cultured on NA media, and paper disks that had previously been soaked in clindamycin (control +) and 0%, 6%, 8%, and 10% green tea extract cream were placed on the agar media. The culture was then incubated for 24 hours at 37°C, and the inhibition zone was checked with a caliper. Results show that green tea extract has positive tests for flavonoids, alkaloids, saponins, and tannins. The optimum concentration of extract cream on antibacterial activity against S. epidermidis and P. acne is 10%. Inhibition zone comparison showed a significant difference between the diameter of the inhibition zone of S. epidermidis and P. acne, p = 0,00485 (p < 0,05), which means that green tea extract cream is better at fighting P. acne.